No correlation between statin exposure and incident diabetes mellitus in HIV‐1‐infected patients receiving combination antiretroviral therapy. Issue 8 (29th March 2016) - Calza, L; Colangeli, V; Magistrelli, E; Manfredi, R; Bon, I; Re, MC; Viale, P
Abstract : Objectives: Recent clinical studies and one meta‐analysis have shown a modest but significant increase in the incidence of diabetes mellitus associated with statin exposure, so this correlation was investigated in a cohort of HIV‐positive subjects. Methods: A retrospective cohort study including adult HIV‐1‐infected patients followed at our Clinic of Infectious Diseases between 2007 and 2014 was performed. Results: We assessed 3170 HIV‐positive patients with a median follow‐up of 5.2 years. The incidence of diabetes mellitus was 1.2 per 100 person‐years and it was not significantly associated with the prescription of statins [hazard ratio (HR) 1.09 per year of statin exposure; 95% confidence interval (CI) 0.7–1.49; P = 0.067], while it was associated with older age, chronic hepatitis C, antiretroviral‐naïve vs . antiretroviral experienced condition, high body mass index, and high serum concentration of triglycerides. Conclusions: In our study, a higher risk of diabetes mellitus was not associated with statin treatment, but with some traditional risk factors.